Training of referees in wrestling - Andrii Ievtyfiiev (Kharkiv State Academy of Physical Culture, 2016)
Purpose: the analysis of problems in the training of referees in wrestling. Material & Methods: theoretical analysis and generalization of literary sources, pedagogical observation. Results: the analysis and generalization of the opinions of experts shows that the success of the complex of judicial activities caused by the judges' experience, knowledge of the techniques and tactics of wrestling and a high level of development of professionally important psycho-physiological functions. Conclusions: given the lack of professional officiating freestyle and Greco-Roman wrestling, the preference shall be given independent forms of training short-term precompetitive workshops not only for training, but and for testing of individual capabilities of individual judges.